Drug information for teens : health tips about the physical and mental effects of substance abuse - Lawton, Sandra Augustyn (Detroit : Omnigraphics, 2006)
Drug information for teens. Second Edition updated facts about drug use, abuse, and addiction. It describes the physical and psychological effects of alcohol, tobacco, marijuana, inhalants, ecstasy and many other drugs and chemicals that are commonly abused. It includes information about drug-related health concerns, such as HIV infection,risky sexual behavior and drug facilitated rape.
Contenido Part I. What you should know about substance abuse and addiction. Part II. Abused Drugs and Chemicals Parte III. Alcohol Parte iV Tobacco Parte V Other drug related health concerns Parte VI Tretment for substance abusers
Incluye index
Keywords: DROGAS; MARIHUANA; ALUCINÓGENOS; INHALANTES; DRUG - EFFECTS